High‐Efficiency Non‐Toxic 2‐Terminal and 4‐Terminal Perovskite‐Transition Metal Dichalcogenide Tandem Solar Cells. Issue 5 (20th February 2022) - Jayan K, Deepthi
Abstract: The modeling tool, SCAPS 1D, is applied to simulate a monolithic 2‐T and mechanically stacked 4‐T tandem solar device architectures with methyl ammonium germanium iodide (MAGeI3 ) perovskite as the active layer of the top cell and transition metal dichalcogenide as the active layer of the bottom cell. To establish the requirement of current density matching between the two subcells of the monolithic 2‐T configuration, a recombination layer composed of indium doped tin oxide (ITO) is also introduced. The thickness of the MAGeI3, TMD, and ITO are optimized to 950, 340, and 100 nm to achieve the current matching condition. The 2‐T device configuration is able to establish a high fill factor (FF) and power conversion efficiency (PCE) of 86.19% and 27.09% after optimizing the physical parameters of the layers. The 4‐T mechanically stacked tandem architecture is also simulated using the SCAPS 1D tool and a maximum possible PCE of 35.11% is achieved after optimizing the physical parameters of the light captivating layers, viz. thickness, the number density of defects and dopants, and the operating conditions viz. temperature, parasitic resistances, and work function of the materials employed as rear contacts. Abstract : This work covers the simulation of tandem solar cells with a perovskite light absorber layer methyl ammonium germanium iodide (MAGeI3 ) and a transition metal dichalcogenide, MoTe2 . The 2‐T tandem configuration provides a high FF and PCE of 86.19% and 27.09% after optimization of the input parameters of the layers and the 4‐T tandem architecture furnishes an excellent PCE of 35.11% .